Smart Costing Kit: game based learning for cost and management accounting / Rafizan Abdul Razak, Eley Suzana Kasim and Dalila Daud - Abdul Razak, Rafizan; Kasim, Eley Suzana; Daud, Dalila (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Cost and management accounting courses are incorporated in the accounting syllabus for both accounting and non-accounting students. One of the challenges in teaching cost and management accounting to the nonaccounting students is the general fear of accounting subject. Notwithstanding, most of the students still viewed accounting as an interesting subject. Hence, the learning problem faced by students needs to be addressed in a fun yet beneficial way. As such, the objective of this study is to assess the effectiveness of using the “Smart Costing Game” as a learning method to overcome this problem. The Smart Costing Game Kit was developed as a learning tool to enable students to correctly classify costs according to certain criteria and subsequently used the cost figures to compute total costs, profit and selling price. Four business settings are chosen consisting of bakery, restaurant, laundry and clinic. At the end of the game activities, the students are required to complete an online survey. Results from the survey demonstrated that the majority of the students agreed that the games were found to be more effective, motivating and engaging than traditional teaching. This implies that students have strong preferences in the use of educational games that added value to the costing subject. These results support the inclusion of Smart Costing Game as a successful learning strategy in cost and management accounting courses for the non-accounting students.